Karakterisasi Morfologi Eichhornia crassipes di Cilacap, Jawa Tengah - Aprianti, Kirani; Agatha Sih Piranti; Elly Proklamasiningsih (Biotropic : The Journal of Tropical Biology, 2025)
Water hyacinth (Eichhornia crassipes) is a widespread aquatic weed in tropical and subtropical regions, which has caused various environmental problems. This study aimed to observe and describe the morphological characteristics of water hyacinth from the waters of Cilacap. The methods used were field observations and analysis of water hyacinth plant samples. The morphological parameters measured included leaf length, petiole length, and root length. The results showed that the average leaf length of water hyacinth in Cilacap was 14 cm, petiole length was 24 cm, and root length was 26 cm. A total of 30 individuals were sampled in this study, with leaf lengths ranging from 10 to 20 cm, petiole lengths ranging from 20 to 28 cm, and root lengths ranging from 22 to 30 cm. These values are consistent with previous reports on the morphology of water hyacinth in tropical waters. This study is important because the environmental conditions of Cilacap waters, such as an average water temperature of 28°C and a water pH of 7.2, can affect the local growth of water hyacinth. The results of this study provide an overview of local morphological variations and can be used as a basis for the management and control of water hyacinth in Cilacap waters.